(untitled) - Pavla Kudlová; Ilona Kočvarová; Věra Vránová; Milan Kudela (University of Ostrava, 2021)
Aim: The goal of this study was to establish the level of awareness amongst pregnant women in terms of preparation for an oral glucose tolerance test (oGTT), compare the results of two waves of data collection, and identify the most frequent preanalytical mistakes made in connection to the oGTT. Design: Comparison of 2 cross-sectional studies. Methods: From 2013-2017 two independent questionnaire studies were performed on a total of 477 pregnant women in the Olomouc and Zlín regions. A total of 225 respondents took part in Study 1 (2013-2014), and a total of 252 in Study 2 (2016-2017). Acquired data was analysed using descriptive statistics focused on the substantive significance of the results, as well as inference statistics. Results: Based on the sum index, the overall level of awareness had increased slightly amongst the women in Study 2 (by 0.41 points out of 5), Cohen's d = 0.3 suggests the effect was only mediocre. Fifteen erroneous processes were found. However, these had a decreasing trend once the guidelines had been unified. Conclusion: A more reliable performance of the oGTT in certified laboratories was declared by the respondents in Study 2. The level of awareness, and checking on their adherence to the regime before and during the course of measuring the oGTT in pregnant women was still inadequate. It is necessary to improve pregnant women's awareness of how to perform the oGTT correctly to ensure the least possible distortion of the results.